2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6091878
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular electrical stimulation training results in enhanced activation of spinal stabilizing muscles during spinal loading and improvements in pain ratings

Abstract: Low back pain is associated with dysfunction in recruitment of muscles in the lumbopelvic region. Effective rehabilitation requires preferential activation of deep stabilizing muscle groups yet training these muscles poses challenges in a clinical setting. This study was carried out in order to quantify the response of deep stabilizing muscles (transverses abdominis and deep fibres of multifidus) to a period of training using a novel neuromuscular electrical stimulation (NMES) application in a group of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 20 publications
6
40
0
Order By: Relevance
“…Previous studies have reported on the ability of transcutaneous NMES applied to the lateral abdominal surface to activate deep lumbar stabilizing muscles [16,17,18,19]. Porcari et al [16] reported significant improvements in muscular strength and endurance of the abdominal region, after applying a belt type NMES to the abdominal wall.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have reported on the ability of transcutaneous NMES applied to the lateral abdominal surface to activate deep lumbar stabilizing muscles [16,17,18,19]. Porcari et al [16] reported significant improvements in muscular strength and endurance of the abdominal region, after applying a belt type NMES to the abdominal wall.…”
Section: Discussionmentioning
confidence: 99%
“…Porcari et al [16] reported significant improvements in muscular strength and endurance of the abdominal region, after applying a belt type NMES to the abdominal wall. Coghlan et al [18,19] reported that NMES applied to the abdominal wall and paralumbar area induced increases in thickness of abdominal deep lumbar stabilizing muscles and lumbar multifidus muscles. However, the ability of transcutaneous NMES, applied to the lumbar paraspinal region, to activate deep lumbar stabilizing muscles has not been investigated thoroughly.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations